Selective screening of coal to improve the washability characteristics at different levels of size reduction. Issue 10 (3rd October 2022) - Sriramoju, S. K.; Singh, Rashmi; Sengupta, M.; Akhter, S.; Dash, P. S.
ABSTRACT: In coal beneficiation, ash content is the main focus area as it plays a vital role in controlling the yield and quality of the washed clean coal. Indian sub-bituminous and bituminous coals are of low-grade with intrinsically distributed ash-bearing minerals, which makes it difficult to segregate the low ash coal. Different stages of crushing and grinding techniques have been used to produce the desired feed size of coal washeries, i.e., −13 mm. During blasting and crushing, cracks propagate through the weaker interfaces within the coal particles. Petrographic analysis suggests the formation of good amount of naturally liberated maceral-rich particles of −13 mm size at different stages. These particles generated at mine site and primary crusher are subjected to further crushing during subsequent stages of secondary and tertiary crushing, resulting in more fine generation and higher energy consumption. Hence, an attempt has been made to check the washability characteristics of coals at different stages of crushing and effect of prescreening of coarse (−13 + 0.5 mm) and fine (−0.5 mm) fraction on washability characteristics of coal and overall clean coal yield. It was observed that −13 mm particles generated at early stage of crushing show good washability characteristics compared to the crushed lump coal (+13 mm) for the separation of 17.8–18% ash clean coal; and hence, prescreening of −13 mm prior to tertiary crushing improves the process efficiency.